PSIKOLOGI PENDIDIKAN DALAM AL-QUR’AN - Muhammad Faisal M. Abdullah (Psympathic : Jurnal Ilmiah Psikologi, 2014)
The core issues have been examined in this study including the relationships of the teacher’s involvement in decision making, interpersonal communication, and work motivation of the BPKB teachers in Gorontalo Province. This study used survey method with correlation techniques. The sample was the whole population of the 47 teachers by using total sampling or sample saturated. Based on the analysis of data concluded results namely 1) there is a positive relationship between teacher’s involvements in decision-making with the work motivation. 2) There is a positive relationship between interpersonal communication and the work motivation of teachers, 3) There is a positive relationship between involvement in decision-making and interpersonal communication simultaneously on the work motivation of teachers. These results indicated that the higher of teachers’ involvement in decision-making and interpersonal communication, the work motivation is increasing.